A Juridical Analysis of Rehabilitation Policy as an Alternative to Criminal Punishment for Narcotics Abusers from a Restorative Justice Perspective - Syaiful Kurniawan; Abu Nawas; Muh Nasir (UIN Jakarta, 2026)
Rehabilitation policy as an alternative to criminal punishment for narcotics abusers has a strong juridical foundation and is aligned with the principles of restorative justice. However, its effective implementation requires regulatory harmonization, capacity building of law enforcement officers, and adequate rehabilitation facilities. This study aims to analyze the juridical framework of rehabilitation policies for narcotics abusers from a restorative justice perspective. The main issues addressed are: (1) how medical rehabilitation for drug addicts is implemented in legal practice, and (2) what obstacles hinder its implementation and law enforcement efforts. This research employs a normative juridical method using statutory and conceptual approaches. Legal materials consist of primary sources, including laws and regulations on narcotics and rehabilitation, and secondary sources such as literature, journals, and legal documents. Data were analyzed qualitatively using a descriptive-analytical method. The findings indicate that rehabilitation policies are legally recognized as a form of protection for narcotics abusers, who are essentially victims. Nevertheless, challenges persist, including punitive-oriented perspectives among law enforcement, limited rehabilitation facilities, and suboptimal inter-agency coordination. A restorative justice approach offers a more humane resolution by emphasizing recovery, social reintegration, and the reduction of the negative impacts of imprisonment. Keywords: Rehabilitation, Narcotics Abusers, Alternative Sentencing, Restorative Justice.